Effects of Rainfall Manipulation on Ecosystem Respiration and Soil Respiration in an Alpine Steppe in Northern Tibet Plateau - Li, Xueqin; Yan, Yan; Fu, Lijiao (Frontiers in Ecology and Evolution, 2021)
The response mechanism of ecosystem respiration (Re) and soil respiration (Rs) to different water conditions is of great significance for understanding the carbon cycle under future changes in precipitation patterns. We used seven precipitation treatments to investigate the effects of precipitation on Re and Rs on a typical alpine steppe in Northern Tibet. Precipitation was captured and relocated to simulate precipitation rates of -25%, -50%, -75%, 0% (CK), +25%, +50%, and +75%. Soil moisture was influenced by all precipitation treatments. There was a positive linear relationship between soil moisture and Re, Rs in the study area during the experiment (July‒October). Soil volumetric water content (VWC), absolute water content (AWC), soil temperature (ST), aboveground biomass (AGB), bulk density, soil total nitrogen (TN), and alkaline hydrolysis nitrogen (AHN) were predictors of Re and Rs. Multiple linear regression analysis showed that ST and AWC could explain 90.6% of Rs, and ST, AWC and AHN could explain 89.4% of Re. Re was more sensitive to increased precipitation(+29.5%) whereas Rs was more sensitive to decreased precipitation(-23.8%). An appropriate increases in water (+25% and +50%) could improve Re and Rs, but a greater increase (+75%) would not have a significant effect; it could have an effect even lower than those of the first two. Our study highlights the importance of increased precipitation and the disadvantage of decreased precipitation on Re and Rs in an arid region. Precipitation changes will lead to significant changes in soil properties and aboveground biomass, and affect Re and Rs, so as to change the climate of the alpine steppe in Northern Tibet in the future. These findings contribute to our understanding of regional patterns of environmental C exchange and soil C flux under climate change scenarios and highlight the importance of water availability to regulating ecosystem processes in semi-arid steppe ecosystems. In view of these findings, we urge future researchers to focus on manipulating precipitation over longer time scales, seasonality, and incorporating more environmental factors to improve our ability to predict and model Re and Rs and feedback from climate change.